Pharmacological targeting of peptidylarginine deiminase 4 prevents cancer-associated kidney injury in mice. (3rd August 2017) - Cedervall, Jessica; Dragomir, Anca; Saupe, Falk; Zhang, Yanyu; Ärnlöv, Johan; Larsson, Erik; Dimberg, Anna; Larsson, Anders; Olsson, Anna-Karin
ABSTRACT: Renal insufficiency is a frequent cancer-associated problem affecting more than half of all cancer patients at the time of diagnosis. To minimize nephrotoxic effects the dosage of anticancer drugs are reduced in these patients, leading to sub-optimal treatment efficacy. Despite the severity of this cancer-associated pathology, the molecular mechanisms, as well as therapeutic options, are still largely lacking. We here show that formation of intravascular tumor-induced neutrophil extracellular traps (NETs) is a cause of kidney injury in tumor-bearing mice. Analysis of clinical biomarkers for kidney function revealed impaired creatinine clearance and elevated total protein levels in urine from tumor-bearing mice. Electron microscopy analysis of the kidneys from mice with cancer showed reversible pathological signs such as mesangial hypercellularity, while permanent damage such as fibrosis or necrosis was not observed. Removal of NETs by treatment with DNase I, or pharmacological inhibition of the enzyme peptidylarginine deiminase 4 (PAD4), was sufficient to restore renal function in mice with cancer. Tumor-induced systemic inflammation and impaired perfusion of peripheral vessels could be reverted by the PAD4 inhibitor. In conclusion, the current study identifies NETosis as a previously unknown cause of cancer-associated renal dysfunction and describes a novel promising approach to prevent renal failure in individuals with cancer.